Endoscopic sinus surgery outcomes in patients with chronic rhinosinusitis and immunoglobulin deficiencies - Shireen Samargandy; Elysia Grose; Jonathan Yip; John M. Lee (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients with chronic rhinosinusitis (CRS) and immunoglobulin deficiencies (ID) have more recalcitrant sinonasal disease and a subset of these patients undergo surgical management for their CRS. However, there is a paucity of literature on the surgical outcomes in this patient population and appropriate treatment algorithms for CRS in patients with ID. The objective of this study was to better elucidate the outcomes of endoscopic sinus surgery (ESS) in patients with ID in terms of disease-specific quality-of-life scores and the need for revision surgery. Methods A case–control study was performed comparing adult patients with ID and healthy controls that had undergone ESS for CRS. Patients were matched based on age, sex, CRS phenotype, and preoperative Lund-Mackay score. The revision surgery rates, time to revision surgery, and changes in sinonasal outcome tests (SNOT-22) were evaluated. Results Thirteen patients with CRS and ID were matched to 26 control patients with CRS. The revision surgery rate for cases and controls was 31% and 12%, respectively, but there was no statistical difference (p > 0.05). There was a clinically meaningful reduction in SNOT-22 scores in both groups from the preoperative to postoperative period [mean of 12 points in patients with ID (p = 0.323) and 25 points in controls (p < 0.001)], however, there was again no significant difference between cases and controls (p > 0.05). Conclusion Our data suggests that patients with ID have clinically meaningful improvement in SNOT-22 scores after ESS but may have higher revision rates than immunocompetent patients with CRS. ID are rare disease entities, thus most attempts at studying this cohort would be limited by sample size. Further homogenous data on immunoglobulin deficient patients is required for future meta-analysis to better understand the impact of ESS in patients with ID.